Cation Size Effects on the Electronic and Structural Properties of Solution‐Processed In–X–O Thin Films. (5th June 2015) - Smith, Jeremy; Zeng, Li; Khanal, Rabi; Stallings, Katie; Facchetti, Antonio; Medvedeva, Julia E.; Bedzyk, Michael J.; Marks, Tobin J.
<x xml:space="preserve">Abstract</x> The nature of charge transport and local structure are investigated in amorphous indium oxide‐based thin films fabricated by spin‐coating. The In–X–O series where X = Sc, Y, or La is investigated to understand the effects of varying both the X cation ionic radius (0.89–1.17 Å) and the film processing temperature (250–300 °C). Larger cations in particular are found to be very effective amorphosizers and enable the study of high mobility (up to 9.7 cm2 V−1 s−1) amorphous oxide semiconductors without complex processing. Electron mobilities as a function of temperature and gate voltage are measured in thin‐film transistors, while X‐ray absorption spectroscopy and ab initio molecular dynamics simulations are used to probe local atomic structure. It is found that trap‐limited conduction and percolation‐type conduction mechanisms convincingly model transport for low‐ and high‐temperature processed films, respectively. Increased cation size leads to increased broadening of the tail states (10–23 meV) and increased percolation barrier heights (24–55 meV) in the two cases. For the first time in the amorphous In–X–O system, such effects can be explained by local structural changes in the films, including decreased In–O and In–M (M = In, X) coordination numbers, increased bond length disorder, and changes in the MOx polyhedra interconnectivity.